Family Dynamics and Social Cohesion in the Intermarriage of Indonesian Muslims in Australia: Revalidating Ibnu Khaldun’s Theory of Asabiyyah - Wardatun, Atun; Ali, Jan A.; Firdawaty, Linda; Maghfurrohmah, Maghfurrohmah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This paper examines the practice of intermarriage, between Indonesian Muslims and non-Indonesian converted Muslims living in Australia. Very little is known about this intermarriage phenomenon and its internal dynamics and patterns of social interaction. Building on Ibn Khaldun’s concept of asabiyyah (group solidarity) that intermarriage can be understood as an intimate link between social groups leading to social cohesion, the paper argues that intermarriage decreases the salience of cultural distinctions and couples and in-group members lose the negative attitudes they may have had toward the out-groups. The research is an empirical study which was conducted through in-depth interviews with 12 married couples, focus group discussions, and observations and yields two key conclusions. First, varying levels of challenges specifically favourable, mildly demanding, moderately trying, and highly challenging establish family dynamics in which the dual-integrated approach to family resilience is enacted. Social circles strongly influence the religious commitment and faith of mixed marriage families, presenting the most problematic distinctions to address. Second, the social cohesion they formed is diverse and strengthens across generations, which impacts on the social and cultural identities of the future offspring who will end up with mixed or multi-ethnic origins. Thus, this article argues that the intermarried partners, although were from different social, cultural, and ethnic, backgrounds, demonstrably shared some common values and aspirations which acted as building-blocks for unity and contributed to in-group and out-group social cohesion.